Teachers’ perception and practice of assessing speaking skills in EFL classrooms: A case study at Wollo University, Ethiopia - Yimer, Ayalew; Regassa, Taye (Educational Challenges, 2025)
Introduction. This study investigates the perceptions and classroom practices of English as a Foreign Language (EFL) instructors at Wollo University, Ethiopia, regarding the assessment of speaking skills. Purpose. The purpose of the research is twofold: to evaluate the alignment between instructors’ theoretical beliefs about speaking assessment and their actual practices, and to identify systemic and pedagogical barriers that undermine effective oral proficiency evaluation. Methodology. Adopting a mixed-methods methodology, the study collected data from 20 instructors and 25 students through structured questionnaires, non-participant classroom observations, and in-depth interviews. Quantitative data were analyzed using descriptive and correlational statistics, while qualitative responses were thematically coded. Results. The results demonstrate that while instructors universally emphasize the importance of speaking assessments for developing communicative competence, their implementation is largely restricted to logistically manageable methods such as group discussions (used by 90% of instructors) and oral presentations (75%). In contrast, more nuanced techniquessuch as role-plays (20%) and individualized interviews (15%) were rare due to reported constraints. Key challenges included time limitations (85% of instructors), large class sizes (80%), inadequate training in assessment design (70%), and limited institutional support for formative feedback. A weak but significant positive correlation (r = 0.135, p <0.05) between instructors’ perceptions and practices underscores the gap between intent and action. Conclusion. The conclusions advocate for institutional interventions, including mandatory teacher training programs on alternative assessment models (e.g., digital portfolios, peer assessments), policy reforms to reduce class sizes, and the integration of automated tools. By bridging this gap, the study argues, universities can better align assessment practices with pedagogical goals, ultimately enhancing students’ oral proficiency in EFL contexts.